Associations between speed, power and endurance performance in super league soccer players - Saidi, Nur Fatihah; Chee, Hian Tan; Raja Azidin, Raja Mohammed Firhad; Ismail, Hashbullah; Choo, Yee Yu; Geik, Yong Ang (UiTM Press, 2022)
The physical characteristics favourable for soccer players includes high level of speed, explosive jumping power, and aerobic fitness which highlights the importance of assessing these characteristics for strength and conditioning training program development. The aim of this study is to examine the associations between speed, power and endurance performance of Malaysia Super League soccer players. Twenty-four male soccer players (age = 24.50 ± 3.11 years, height = 176.12 ± 8.11 cm, body mass = 70.86 ± 9.07 kg) were recruited in this study and all the players were tested for explosive lower body power (vertical jump, VJ), speed (30meter sprint), and endurance (Yo-Yo Intermittent Endurance level 2, YYIEL2). A statistically significant correlation was found between 30-meter sprint time and distance covered in YYIEL2, but contrary to previous findings reported in the literature, sprint time and VJ height were not correlated. Therefore, VJ training may not necessarily improve speed and an improvement in VJ performance may not reflect an improvement in speed. In addition, no significant correlation was found between VJ height and the distance covered in YYIEL2. Given the intermittent nature of the game, the negative moderate correlation between sprint time and distance covered in YYIEL2 (r = -0.43, p <0.05) indicated that specific aerobic and anaerobic performance could be enhanced simultaneously through the appropriate training programme.